2016
DOI: 10.18632/oncotarget.9361
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ZC3H15 increases HCC growth and predicts poor survival after surgical resection

Abstract: Zinc finger CCCH-type containing 15 (ZC3H15), also known as DRG family regulatory protein 1 (DFRP1), is a highly conserved eukaryotic protein that associates with active translation machinery. The aim of our study was to explore the clinical relevance and intrinsic functions of ZC3H15 in hepatocellular carcinoma (HCC). We constructed a cohort with 261 tumor and matched normal tissues from HCC patients. ZC3H15 protein and mRNA levels were determined using immunohistochemistry, western blot analysis, and quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 32 publications
(30 reference statements)
2
19
0
Order By: Relevance
“…The biological mechanism of ZC3H15 in human cancers remains largely unclear. Bei et al used a microarray to evaluate the functional role of ZC3H15, and they found that ZC3H15 was involved in several critical signaling pathways, such as WNT pathway, NF-κB pathway, EGF pathway, TGF-β pathway, and PDGF pathway [18]. Here, we demonstrated that silencing of ZC3H15 reduced the protein expression levels of c-Myc and its downstream molecules such as CDK4, CDK6, and CyclinD1 in GC cells.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The biological mechanism of ZC3H15 in human cancers remains largely unclear. Bei et al used a microarray to evaluate the functional role of ZC3H15, and they found that ZC3H15 was involved in several critical signaling pathways, such as WNT pathway, NF-κB pathway, EGF pathway, TGF-β pathway, and PDGF pathway [18]. Here, we demonstrated that silencing of ZC3H15 reduced the protein expression levels of c-Myc and its downstream molecules such as CDK4, CDK6, and CyclinD1 in GC cells.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, Gianni et al has revealed the interaction of ZC3H15 with TRAF2, which was responsible for the activation of NF-κB signaling [13][14][15][16][17]. Indeed, ZC3H15 act as an important role involved in cell proliferation, apoptosis, cell adhesion, and transcription, and dysregulation of ZC3H15 has been reported in hepatocellular carcinoma (HCC) and acute myeloid leukemia (AML) [18]. However, the biological role of ZC3H15 expression in GC is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The DRG GTPases have been implicated in a variety of cellular processes including cell growth and proliferation. Several papers have suggested that DRG1, DRG2 and DFRP1 are required for the growth and proliferation of various cancer cell lines [56,[84][85][86][87][88]. Together, these reports suggest that DRG GTPases promote the growth and viability of proliferating cells.…”
Section: Cell Proliferation and Cancermentioning
confidence: 94%
“…DFRP1 is overexpressed in hepatocellular carcinomas where high expression is correlated with decreased survival [ 86 ]. In a hepatocellular cell line knockdown of DFRP1 results in reduced cell proliferation in addition to causing an increase in apoptosis [ 86 ]. Depleting DFRP1 also reduced the growth of tumors in mice [ 86 ].…”
Section: Roles Of Drgs and Dfrps In Diseasementioning
confidence: 99%
“…Among all patients, tumor size ranged from 1.5 to 13.8 cm (median size, 6.0 cm). Tumor differentiation was classified as high differentiation, moderate differentiation or low differentiation ( 14 ). According to the Barcelona Clinical Liver Cancer system (BCLC), HCC was classified as early stage (BCLC A), intermediate stage (BCLC B), or advanced stage (BCLC C) ( 4 ).…”
Section: Methodsmentioning
confidence: 99%